Vision of a near future: Bridging the human health–environment divide. Toward an integrated strategy to understand mechanisms across species for chemical safety assessment. (February 2020) - Rivetti, Claudia; Allen, Timothy E.H.; Brown, James B.; Butler, Emma; Carmichael, Paul L.; Colbourne, John K.; Dent, Matthew; Falciani, Francesco; Gunnarsson, Lina; Gutsell, Steve; Harrill, Joshua A.; Hodges, Geoff; et al.
Abstract: There is a growing recognition that application of mechanistic approaches to understand cross-species shared molecular targets and pathway conservation in the context of hazard characterization, provide significant opportunities in risk assessment (RA) for both human health and environmental safety. Specifically, it has been recognized that a more comprehensive and reliable understanding of similarities and differences in biological pathways across a variety of species will better enable cross-species extrapolation of potential adverse toxicological effects. Ultimately, this would also advance the generation and use of mechanistic data for both human health and environmental RA. A workshop brought together representatives from industry, academia and government to discuss how to improve the use of existing data, and to generate new NAMs data to derive better mechanistic understanding between humans and environmentally-relevant species, ultimately resulting in holistic chemical safety decisions. Thanks to a thorough dialogue among all participants, key challenges, current gaps and research needs were identified, and potential solutions proposed. This discussion highlighted the common objective to progress toward more predictive, mechanistically based, data-driven and animal-free chemical safety assessments. Overall, the participants recognized that there is no single approach which would provide all the answers for bridging the gap between mechanism-based human health and environmental RA, but acknowledged we now have the incentive, tools and data availability to address this concept, maximizing the potential for improvements in both human health and environmental RA. Graphical abstract: Unlabelled Image Highlights: Thirty representatives from diverse fields and affiliations gathered to discuss holistic chemical safety decisions. Key challenges, current gaps and research needs were identified, and potential solutions proposed. It was agreed that while no single solution will answer all the problems, we now have the tools to start addressing them.